ANALYSIS OF LANE KEEPING AND SEGMENTATION INFORMATION SYSTEMS TO SOLVE THE PROBLEM OF IMPROVING TRAFFIC SAFETY - DREVYCH, LIUBOMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In the modern era, the rapid development of autonomous driving technologies has significantly influenced traffic safety measures. Among the critical components of these technologies are Lane Keeping Systems (LKS) and Lane Segmentation Information Systems (LSIS). These systems play a vital role in preventing accidents caused by lane departures, a prevalent cause of road incidents globally. This analysis aims to explore the efficacy of LKS and LSIS in enhancing traffic safety, focusing on their technological aspects, implementation challenges, and potential benefits.Lane Keeping Systems are designed to assist drivers in maintaining their vehicles within lane boundaries. These systems typically employ sensors, cameras, and artificial intelligence algorithms to monitor lane markings and vehicle position continuously. When a potential lane departure is detected, LKS can provide corrective actions such as steering adjustments or warnings to the driver. The integration of LKS in vehicles has shown a reduction in unintended lane departures, thereby decreasing the likelihood of accidents caused by driver distraction or drowsiness.Similarly, Lane Segmentation Information Systems are integral to the functionality of autonomous and semi-autonomous vehicles. LSIS use advanced image processing techniques to identify and segment lanes from road images captured by cameras. This segmented information is crucial for vehicle navigation, enabling precise lane tracking and maneuvering. By providing accurate lane information, LSIS contribute to the overall situational awareness of the vehicle, enhancing its ability to make informed driving decisions.The synergy between LKS and LSIS is evident in their combined ability to improve traffic safety. While LKS provide real-time lane-keeping assistance, LSIS ensure that the vehicle has an accurate understanding of the road layout. This combination minimizes the risk of lane-related accidents, particularly in complex driving scenarios such as highways and urban intersections.Despite their benefits, the implementation of LKS and LSIS faces several challenges. One major issue is the variability in road conditions and lane markings. Inconsistent or poorly maintained lane markings can impair the effectiveness of these systems. Additionally, adverse weather conditions such as rain, fog, or snow can obstruct the sensors and cameras, leading to potential system failures. Therefore, continuous advancements in sensor technology and image processing algorithms are essential to address these challenges and enhance system reliability.Another challenge lies in the integration of LKS and LSIS with other vehicle systems. Ensuring seamless communication between different systems is crucial for optimal performance. This requires robust software architectures and standardization across different vehicle manufacturers. Moreover, the transition from human-driven to autonomous vehicles necessitates public acceptance and regulatory support. Educating drivers about the capabilities and limitations of LKS and LSIS is vital to build trust and encourage adoption.The potential benefits of LKS and LSIS in improving traffic safety are substantial. By reducing the frequency of lane departure incidents, these systems can lower the overall accident rate. This not only enhances driver and passenger safety but also reduces the economic costs associated with road accidents. Furthermore, the widespread adoption of LKS and LSIS can lead to smoother traffic flow and reduced congestion, contributing to a more efficient transportation system.In conclusion, Lane Keeping Systems and Lane Segmentation Information Systems are pivotal in the pursuit of safer roads. Their ability to prevent lane departures and provide accurate lane information underscores their importance in modern vehicle safety technologies. While challenges exist, ongoing research and development efforts are poised to overcome these hurdles, paving the way for more reliable and effective systems. As these technologies continue to evolve, they hold the promise of significantly enhancing traffic safety and transforming the future of transportation.
Keywords: Road safety; lane keeping assistance system; lane segmentation; road accidents; computer vision; machine learning; image analysis